2013
DOI: 10.1097/mcp.0b013e3283644c6f
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiologic manifestations of cardiac sarcoidosis

Abstract: The electrophysiologist's approach to a patient with cardiac sarcoidosis can aid in diagnosis, risk stratification, and management with antiarrhythmic therapy, catheter ablation, and ICD implantation for the prevention of SCD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2014
2014
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 28 publications
(27 reference statements)
0
21
0
1
Order By: Relevance
“…Conduction system abnormalities in cardiac sarcoidosis can result from direct involvement of the conduction system or ventricular wall from granulomatous infiltration and scar tissue [67]. The prevalence of SCD in cardiac sarcoidosis is reported between 12 and 65 % [68] and primary prevention via ICD implantation is a grade IIA recommendation (level C) [69]. Similarly CCC is associated with chronic inflammation resulting from Trypanosoma cruzi infection.…”
Section: Biomarkers In Sudden Cardiac Deathmentioning
confidence: 99%
“…Conduction system abnormalities in cardiac sarcoidosis can result from direct involvement of the conduction system or ventricular wall from granulomatous infiltration and scar tissue [67]. The prevalence of SCD in cardiac sarcoidosis is reported between 12 and 65 % [68] and primary prevention via ICD implantation is a grade IIA recommendation (level C) [69]. Similarly CCC is associated with chronic inflammation resulting from Trypanosoma cruzi infection.…”
Section: Biomarkers In Sudden Cardiac Deathmentioning
confidence: 99%
“…Villes‐Gonzalez et al reported that 32% of CS patients developed a supraventricular arrhythmia during a mean 5.8‐year follow‐up, and 23% of these arrhythmias were due to either atrial fibrillation or flutter . These findings are corroborated by other studies . The lifetime risk of developing atrial fibrillation or flutter in the general population has been estimated at 26% in men and 23% in women, similar to the prevalence in the CS population …”
Section: Alterations In Cardiac Conductionmentioning
confidence: 63%
“…Sarcoidosis often affects the cardiac conduction system and causes a variety of clinical presentations ranging from normal electrocardiograms to complete atrioventricular (AV) block . Granuloma formation in the basal interventricular septum is thought to be the major mechanism of conduction disorders, with the location and burden of disease of the AV nodal arterial supply, the AV node itself, and/or the His‐Purkinje system determining the degree of dysfunction …”
Section: Alterations In Cardiac Conductionmentioning
confidence: 99%
See 2 more Smart Citations